Ethical theory and business - Arnold, Denis G., (Cambridge University Press, 2020)
For forty years, successive editions of Ethical Theory and Business have helped to define the field of business ethics. The 10th edition reflects the current, multidisciplinary nature of the field by explicitly embracing a variety of perspectives on business ethics, including philosophy, management, and legal studies. Chapters integrate theoretical readings, case studies, and summaries of key legal cases to guide students to a rich understanding of business ethics, corporate responsibility, and sustainability. The 10th edition has been entirely updated, ensuring that students are exposed to key ethical questions in the current business environment. New chapters cover the ethics of IT, ethical markets, and ethical management and leadership. Coverage includes climate change, sustainability, international business ethics, sexual harassment, diversity, and LGBTQ discrimination. New case studies draw students directly into recent business ethics controversies, such as sexual harassment at Fox News, consumer fraud at Wells Fargo, and business practices at Uber.